Mettre en lumière les zones d’ombre du service public de l’emploi - Claire Vivés (La Nouvelle Revue du Travail)
Pôle emploi ne quittez pas and Les Règles du jeu are two French-language documentaries showing how unemployment is being tackled in France today. Analysis of these two works reveals a sharp contrast – one that is beneficial to private providers - between work situations for public sector officers and the kinds of support that unemployed persons receive from a public institution (Pôle emploi) as opposed to what they would get from a private provider. The text complements the documentary makers’ understanding of realities by mobilizing a quantum of sociological knowledge. It demonstrates that the contrast being highlighted here results from work organisation choices and from differences in providers’ financial resources. More broadly, the approach adopted here raises questions about how case management is handled where unemployed people are concerned. It also looks at the public sector dimension of a public employment service to illustrate the destabilisation affecting this institution.